Islam, gay, and marginalization: a study on the religious behaviours of gays in Yogyakarta - Koeswinarno Koeswinarno; Mutolehudin Mustolehudin (Indonesian Journal of Islam and Muslim Societies, 2017)
0px; " Man does not intend to be born gay, whose existence is not welcomed in the society including within his spiritual religious expressions. In Wonosobo, in the year of 2016, a marriage ceremony almost happened between a male and a male. This phenomenon is interesting to be studied in detail. In a specific way, this article uncovers the religious behaviours of gays in Yogyakarta. Usingan anthropological approach, the researchers were directly involved in the subjects’ lives in the social, economic, cultural, and religious aspects. In texts, same-sex relationships were found in the narratives of Prophet Luth written in the Al-Quran books Al-A’raf verse 81, Al-Shu’ara’ verses 165-166, An-Nisa verse 16, and Hud verses 77-83. These verses are used as the basis for rejecting homosexuality. From the social life happening in Yogyakarta there arise conflicts between the gays and their families so that they run away from their families to join gay communities and form economic and even religious groups.Furthermore, in their citizenship status, there is marginalization or administrative abuse for their identities in the identification card.Manusia tidak berniat untuk dilahirkan sebagai gay, yang keberadaannya tidak disambut baik di masyarakat termasuk dalam ungkapan spiritualnya. Di Wonosobo, pada tahun 2016, sebuah upacara pernikahan hampir terjadi antara sesama jenis lelaki. Fenomena ini menarik untuk dikaji secara detail. Artikel ini mengungkap perilaku religius kaum gay di Yogyakarta. Dengan menggunakan pendekatan antropologis, peneliti secara langsung terlibat dalam kehidupan subyekdalam aspek sosial, ekonomi, budaya, dan agama. Dalam teks, hubungan sesama jenis ditemukan dalam narasi Nabi Luth yang ditulis dalam buku Al-Quran AlA’raf ayat 81, ayat Al-Shu’ara 165-166, An-Nisa ayat 16, dan ayat-ayat Hud 77- 83. Ayat-ayat ini digunakan sebagai dasar untuk menolak homoseksualitas. Dalam kehidupan sosial di Yogyakarta, timbul konflik antara kaum gay dan keluarga mereka. Konflik ini membuat mereka melarikan diri dari keluarga dan bergabung dengan komunitas gay dan membentuk kelompok ekonomi dan bahkan kelompok keagamaan. Dalam status kewarganegaraan, mereka mengalami marginalisasi atau penyalahgunaan administratif dalam kartu identitas mereka.